수퇘지의 정액 성상과 혈중 항산화물 농도에 대한 통마늘분말 급여의 영향 - 박준철; 조규호; 류재원; 홍준기; 이성대; 사수진; 김인철; 이상철; Park, Jun-Cheol; Cho, Kyu-Ho; Ryu, Jae-Weon; Hong, Joon-Ki; et al. (Journal of animal science and technology, 2010)
The objective of this study was to determine the effects of dietary supplementation of whole garlic powder (WGP) on semen characteristics and blood antioxidant level in boars. For this study, nine Duroc boars of 12 months age were used. Semen and blood samples were collected for 13 weeks, once in each week. The boars were fed the basal diet (BD; control) or BD supplemented with 3% WGP. There were no significant differences in the semen volume and sperm concentration between control and WGP group on all collection weeks. However, total sperm number per ejaculate was higher in the WGP group than that in the control group on collection weeks 6, 7 and 8 (P<0.05). Also, on collection weeks 5, 6, 7 and 8, mean of total ejaculated sperm numbers per boar were significantly higher in the WGP group compared to control group (P<0.05). On the other hand, ejaculation frequency per boar (boar's libido) and total ejaculated sperm number per boar were significantly increased in the WGP group compared to the control group, respectively (P<0.05). Although there was no difference in polyphenol level in seminal plasma between two treatment groups, polyphenol level in blood serum was significantly higher in the WGP group on collection weeks 9, 12 and 13 (P<0.05). These results indicate that dietary supplementation of 3% WGP improves boar libido and semen productivity such as ejaculation frequency per boar, total sperm number per ejaculate, mean of total ejaculated sperm number per head, and elevate the blood level of antioxidant (polyphenol) in boar serum. 본 연구는 통마늘분말의 급여가 수퇘지의 정액 성상과 혈중 항산 화물 농도에 미치는 영향을 구명하기 위해 12개월령의 듀록종 수퇘지 9두를 공시하여 시험사료만을 급여한 대조구(4두)와 시험사료에 0.3% 통마늘분말을 첨가하여 급여한 실험구(5두)를 이용해 13주간 수행되었다. 통마늘분말의 급여가 수퇘지의 정액생산량과 정자농도에 미치는 영향을 8주간에 걸쳐 평가한 결과, 정액생산량에서는 통마늘분말 급여 여부에 따른 차이를 보이지 않았으나, 수퇘지 정액의 평균 총정자수는 0~4주의 평균 총정자수는 통마늘분말 급여여부에 상관없이 차이가 없었다. 그러나, 5~8주에 채취된 정액의 평균 총정자수는 통마늘분말을 급여한 실험구가 대조구에 비해 유의적으로 높게 나타났다(P<0.05). 통마늘분말 급여가 수퇘지의 성욕에 미치는 영향을 알아보기 연속 사정횟수와 전체 사출정액에 대한 총정자수를 조사한 결과, 통마늘분말을 급여한 실험구가 대조구에 비해 사정횟수와 총정자수가 유의적으로 높게 나타났다(P<0.05). 수퇘지에 대한 통마늘분말의 급여가 정장 및 혈장 내 polyphenol 농도에 미치는 영향에서는 정장 내에서의 polyphenol 농도는 통마늘분말 급여여부에 상관없이 차이를 보이지 않았다. 그러나, 혈장 내에서의 polyphenol 농도는 9주, 12주 및 13주차에 통마늘분말을 급여한 실험구가 대조구에 비해 유의적으로 높은 수치를 나타내었다(P<0.05). 본 실험의 결과를 종합하면, 정액채취용 수퇘지에 대한 통마늘분말의 급여는 성욕의 향상에 영향을 미쳐 정액채취빈도와 정액내 총 정자수를 증가시키고, 혈액 내 항산화물 농도를 높이는 것으로 나타나, 통마늘분말이 정액채취용 수퇘지의 성적을 향상시키는데 사료적 가치가 있는 것으로 사료된다.